A technology audit of the UP pilot food plant - Tan, Rachel Ong (University of the Philippines Diliman, 2012)
A technology audit was conducted on the UP Pilot Food Plant to assess its overall technological capabilities and to provide recommendations based on the audit findings. The UP PFP serves as the training laboratory for UP Food Technology students, while also providing technical services to industry clients through its food processing, laboratory analysis and product development capabilities. The project was carried out in three phases. Phase 1 involved the internet and library research for technology audit methodologies, selection of the technology audit framework and development of a technology audit questionnaire. The technology audit proper was completed in Phase 2 from audit planning up to the presentation and validation of audit findings. Phase 3 is the last phase of the project concerning the analysis of results and formulation of recommendations. The methodology employed in conducting the technology audit was a combination of the qualitative diagnostic approach by Kelessidis and the quantitative assessment using Garcia-Arreola's Technology Audit Model (TAM) checklist. A technology audit questionnaire was developed with the first part following the Kelessidis' diagnostic approach and the second part as the TAM checklist. The General Diagnosis part of the audit questionnaire included assessment areas such as Human Resources, Qualification, Research and Technological Development, Problems, Technological Needs and Demands of Related Services and Future Trends. An inventory of the PFP's technological assets was also conducted. The second part of the questionnaire representing the TAM Checklist focused on six major categories for assessment. These are the Corporate Environment, Technologies Categorization, Markets and Competitors, Innovation Process, Value-added Functions and Acquisition and Exploitation of Technology. A five point rating scale from 1 to 5 (poor to outstanding) was used to assess each element in the checklist. Descriptions for each rating was also formulated and used as a guide for evaluation. A rating of 1 corresponds to a condition wherein strategies/policies/systems/processes are either not implemented or non-existent. A rating of 2 indicates that strategies/policies/systems/processes are repeatable but intuitive. Possessing strategies/policies/systems/processes that are established, documented, communicated and implemented merits a rating of 3. A rating of 4 means that there is a good monitoring and evaluation system, while a rating of 5 denotes that best practices are observed and there is continuous improvement in the strategies/policies/systems/processes. The PFP's overall TAM score based on the sum for all 46 elements is 103. This represents just 44.8 percent of the perfect score of 230 with 5 as the constant score for all elements. The PFP's score is nearer to the average performance, wherein the score 103 represents 74.6 percent of the overall score of 138 with 3 as the constant score for all elements. A tally of the results based on averaging yield an average score of 2.2 or Below Average. This also means that the PFP strategies, policies, systems and processes are generally repeatable but intuitive. The major findings from this technology audit are described below. The PFP has a documented Mission and Vision statement but this has not been recently reviewed and communicated. Technology is not explicitly defined through a corporate strategy. A technology strategy has also not been formulated. Consequently, there are no objectives established at functional levels to help in monitoring, controlling, evaluating and improving its technological processes to determine if desired results are achieved. The PFP's very lean organization facilitates rapid decision making but also limits the technological expertise within the organization. The position for a Chief Technology Officer is not defined within the organizational chart. Nevertheless, the PFP structure is supported by the PFP Faculty-in-Charge, FSN Chair and the College Dean for major technological decisions and resource needs. The PFP's technologies are generally mature and may soon transform from being the PFP's core technologies into basic technologies, providing the organization with no competitive advantage. The PFP has not been able to exploit the opportunity of tapping the technological knowledge of the College's food science and technology experts due to undefined policies, including policies on knowledge and technology transfer. There is no formal training program to continually build competence levels of the PFP personnel. A systematic process for identifying, acquiring, maintaining, upgrading and exploiting the PFP's technological assets is an area for improvement. There is a lack of focus on addressing actual market needs. Effective planning of R&D projects supported by market studies has not been demonstrated. There is no R&D portfolio that is aligned with the PFP's corporate and technology strategies. The PFP's management is concentrated on operations, with innovation being less prioritized. Benchmarking activities has not been done to determine industry best practices and opportunities for improvement for the PFP. The promotion of environment-conscious technology has not yet been integrated into the PFP's policies.